The Constitutional Rights of the Community Regarding Fair Development Projects: Legal Position and Legal Certainty - Nana Arthana; Sami'an Sami'an; Ganis Vitayanti Noor (International Journal Labs, 2026)
Construction projects inherently involve the public sphere because their outcomes directly impact community safety, welfare, and access to public facilities. Consequently, the fulfillment of constitutional rights—particularly the principles of equality before the law under Article 27(1) of the 1945 Constitution and legal certainty under Article 28D(1)—is essential to ensure that development is carried out fairly. This article examines how these rights are realized or potentially violated through two key regulatory instruments: construction contracts and building permit processes. Using a normative juridical method supported by statutory analysis, doctrinal review, and comparative reference to FIDIC Red Book 2017, the study identifies common sources of constitutional risk such as ambiguous technical specifications, unclear brand corridors, incomplete designs, and procedurally defective permits. The article concludes that strengthening contract documents, enhancing transparency of permitting procedures, and ensuring accountable public oversight are crucial for safeguarding constitutional rights in equitable development.